A Study on Human Resources Management in Tourism & Hospitality Industry: Its Planning, Processing and Developing - Ankit Prakash (International Journal of Asian Business and Management, 2023)
Current work deals in a clear and straightforward manner with the management of human resources in tourism & hospitality industry service organizations, where personnel are related to achieving policies, goals, and objectives. They give a creative and productive spark and are vital to a company's success. This paper is related to the phases of career development and career programs. It reflects the evolution of an individual's work over time and emphasizes the following stages: exploration (trying new roles), foundation, maintenance and descent, delineation of activity by developmental stages, and personal achievement. relationship with age and relative levels of participation